Shawkani’s Method of Use of Recitations in The Context of His Work Named Fath al-Qadir - Keleş, Mehmet (Fırat University, 2024)
Shawkani (d. 1250/1834), one of the leading scholars of Yemen, grew up in an environment where the Zaydism sect was dominant. However, when he was in his thirties, he declared himself a mujtahid, stating that adhering to any sect was imitation. He wrote his copyrighted works within the framework of this thought, and the most comprehensive work among them in terms of content is his commentary book called Fath al-kadîr, which is also the subject of our research. The work in question is known as the only work that shows Shawkani’s method of handling recitation aspects. When we look at the entire work, it is seen that Shawkani frequently uses recitations within the framework of interpreting the verses. In explaining the verses, he sometimes conveys the recitations with various opinions, and sometimes he is content to attribute the differences in recitations only to the person who recites them. He conveys the recitations he deals with by attributing them to many individuals and regions, including the companions, tabiin and qiraat imams. This research is limited to Shawkani’s work called Fath al-kadîr. The analyzed recitation differences were tried to be made through the method of illustration, based on Shawkani’s commentary. It has been concluded that the author, in his commentary, reveals his personal opinion by intensively dealing with the effects of the recitations on the meaning and their reflection on fiqh issues, which he inferred from different issues.

Yemen’in önde gelen âlimlerinden biri olan Şevkânî (ö. 1250/1834), Zeydîlik mezhebinin hüküm sürdüğü bir ortamda yetişmiştir. Ancak otuzlu yaşlara geldiğinde herhangi bir mezhebe bağlı kalmanın taklitçilik olduğunu belirterek kendisini müçtehit olarak ilan etmiştir. Telif ettiği eserlerini bu düşünce çerçevesinde kaleme almış ve bunlar arasında muhteva bakımından en kapsamlı olan eseri ise araştırmamıza da konu olan Fet?u’l-?adîr adlı tefsir kitabıdır. Söz konusu eser, Şevkânî’nin kıraat vecihlerini ele alma yöntemini gösteren tek eseri olarak bilinmektedir. Eserin tamamına bakıldığında Şevkânî’nin ayetleri yorumlama çerçevesinde kıraatleri sık sık kullandığı görülmektedir. Ayetleri açıklama sadedinde kimi zaman kıraatleri çeşitli görüşlerle birlikte aktarırken bazen de kıraat farklılıklarını yalnızca okuyuş sahibine nispet etmekle yetinmektedir. Ele aldığı kıraatleri sahabe, tabiîn ve kıraat imamları olmak üzere birçok şahıs ve bölgeye isnad ederek aktarmaktadır. Bu araştırma, Şevkânî’nin Fet?u’l-?adîr adlı eseriyle sınırlandırılmıştır. Tahlili yapılan kıraat farklılıkları, Şevkânî’nin tefsirinden hareketle örneklendirme yöntemiyle yapılmaya çalışılmıştır. Müellifin tefsirinde, farklı hususlarla istidlâlde bulunduğu kıraatlerin manaya olan etkileri ve fıkhî meselelere yansımasını yoğun bir şekilde işleyerek kişisel görüşünü ortaya koyduğu sonucuna varılmıştır.
FETHU’L-KADÎR ADLI ESERİ BAĞLAMINDA ŞEVKÂNÎ’NİN KIRAATLERİ KULLANMA YÖNTEMİ
Keywords: Turkish Islamic Literature; Türk İslam Edebiyatı